PENGARUH LATIHAN DOT DRILLS DAN SHUTTLE RUN TERHADAP PENINGKATAN KELINCAHAN REAKSI ELAKAN PADA PENCAK SILAT PERSINAS ASAD BANGKALAN - Putra, Freanza Diaz Mahesa; Handayani, Heni Yuli; Hidayatullah, Fajar (JURNAL ILMU KEOLAHRAGAAN, 2024)
This research was conducted to determine whether there was an effect of dot drills and shuttle run training on increasing the Agility of Avoidance Reactions in Pencak Silat Personas Asad Bangkalan. The research was carried out over 8 meetings, this type of research is quasi-experimental research. The research design used was a "two groups pre-test-post-test design". The results of the research show that there is a significant difference between dot drills training and shuttle run training and shuttle run training has an influence on the results of increasing the agility of dodge reactions in Persinas ASAD Bangkalan College fighters. This is proven by obtaining normality test results from the pretest and posttest of 0.200 > 0.05, so the data is normally distributed. As for the homogeneity test obtained with a p-value> 0.05, the data variance was declared homogeneous and hypothesis testing obtained a t-count value of 5.945 and a t-table of 2.365 with a Sig p of 0.00. The results show that there is a significant difference in shuttle run training in increasing the agility of the fighter's dodging reactions at the Persinas Asad Bangkalan College